2000
DOI: 10.1038/sj.ejcn.1601045
|View full text |Cite
|
Sign up to set email alerts
|

Basal metabolic rate and energy costs at rest and during exercise in rural- and urban-dwelling Papua New Guinea Highlanders

Abstract: Objective: (1) To evaluate inter-individual variations, regional and sex differences in the basal metabolic rate (BMR) and related variables; (2) to compare measured BMR with estimated BMR using predictive equations; and (3) to examine the net mechanical ef®ciency (NME) in step tests. Design: BMR and energy costs at rest and during step tests were measured by the Douglas bag technique of indirect calorimetry. NME was calculated from BMR and energy costs of step tests. Setting: Rural villages under subsistence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Some earlier studies also measured energy costs of activities on small numbers of subjects [27][28][29] . However the importance of such data, although on smaller numbers of subjects, needs to be appreciated in view of the scarcity of data on energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some earlier studies also measured energy costs of activities on small numbers of subjects [27][28][29] . However the importance of such data, although on smaller numbers of subjects, needs to be appreciated in view of the scarcity of data on energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…This will facilitate sound comparisons of energy expenditure patterns in different populations. 29 Papua New Guinea (8) 7.51 6 0.4** RMR -resting metabolic rate. *P , 0.05 for comparison with the estimates in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The RMR was measured in the sitting position using indirect calorimetry with the Douglas bag technique (Douglas, 1911;Yamauchi and Ohtsuka, 2000). The measurement was made between 10:00 and 11:00 a.m.…”
Section: Resting Metabolic Rate (Rmr)mentioning
confidence: 99%
“…But, like FAO/S, the H&R equations are limited by their geographically restricted sample, significantly underestimating BMR in Europeans by 5% (Soares et al, 1993). Less easily explained, the H&R equations also overestimate BMR by 6-8% in some tropical groups, while giving underestimates of 4-11% in others (Spurr et al, 1996b;Yamauchi and Ohtsuka, 2000). These equations also estimate BMR to within 0.5% in North Americans from the decidedly non-tropical climates of Philadelphia and Montreal (Soares et al, 1993).…”
mentioning
confidence: 88%
“…Seasonality was impossible to control in the present study, because the season during which each subject's BMR was measured was not often reported. Finally, lifestyle differences related to exposure to extreme conditions appear not to influence BMR adj (Rode and Shephard, 1995;Snodgrass et al, 2005;Yamauchi and Ohtsuka, 2000), nor do differences in level of physical activity (Armellini et al, 2000;Bingham et al, 1989;Gilliat-Wimberly et al, 2001;Pullicino et al, 1996;Smith et al, 1997;Taaffe et al, 1995). …”
mentioning
confidence: 96%